ANALISIS PEMASARAN KOMODITAS CENGKEH DI DESA TALUDAA KECAMATAN BONE KABUPATEN BONE BOLANGO - Tamran Suaib; Yanti Saleh; Amelia Murtisari (Universitas Negeri Gorontalo, 2018)
This research aims to: 1) Knowing clove marketing channel in Taludaa Village Bone District of Bone Bolango District. 2) Analyze margin and distribution of clove marketing margin in Taludaa Village, Bone Sub-District, Bone Bolango District. 3) Knowing the fluctuation of clove prices in Taludaa Village, Bone Sub-District, Bone Bolango District. This research was conducted in Taludaa Village Bone Sub-district of Bone Bolango Regency from September to October of 2017. The method used is survey method that is data collection based on interview and observation. Dotampel sampling technique is done by using Simple Random Sampling method, that is random sampling from all population located in Taludaa Village Bone Sub-district of Bone Bolango Regency where in this study population consists of 52 respondents farmers and taken multiples of 2 so as to get a sample of 26 people . Types and data sources used in this study are primary data and secondary data. Data analysis used to calculate marketing analysis using qualitative descriptive analysis. The results showed that: 1) Clove marketing channel included in the category of indirect marketing. the distribution channel that is the farmer sells to the collector merchant then proceeded to the wholesaler. 2) The marketing margin on clove marketing channel is Rp.5.000 / Kg. 3) Clove prices fluctuate at the farm level. In August the price of cloves jumped by Rp 135.00 / kg, in September the price of cloves dropped slightly by 11.1% at a price of Rp 120,000 / kg from the previous price caused by several factors. In October and November the price of cloves decreased by 4.17% with the price of Rp115.000 / Kg because in that month was the time of harvest and the production in this month greatly increased so that the price of clove is quite stable. So even the price of cloves at the merchant level in August rose as much as Rp 146.000 / Kg influenced by several factors. Clove prices In September decreased slightly 14.38% from August prices at Rp 125,000 / kg. While in October and November the price decreased 4% ie Rp 120.000 / Kg, but relatively stable as the price at the farm level. Some factors that affect the fluctuation of clove prices are not yet arrived harvest time, the number of requests by collectors and weather factors.